Дослідження методу автоматизованого контролю геометричних параметрів з’єднань оптичних волокон з різними характеристиками розповсюдження електромагнітних хвиль - Малик, Б. О.; Токарєва, О. В. (ХНУРЭ, 2016)
The application of diverse optical fibers welding point geometrics testing in the mechanical and technological systems and complexes automation and control systems building. Based on the interference testing methods the fringe patterns sampling techniques are developed and further analysis is conducted. The diverse optical fibers (OF) joint margins measuring method is proposed and software for its implementation is created. The given technique experimental research with optical fibers fringe patterns determination unit and created interference method automation software application is held.
Keywords: оптичне волокно; з'єднання волокон; інтерференційний метод контролю; розповсюдження електромагнітних хвиль